Socio-economic Status of the Patients with Acute Coronary Syndrome: Data from a District-level General Hospital of Bangladesh (Cardiovascular Journal, 2017)
Background: Several studies have reported the correlation between socio-economic status (SES) and incidence of acute coronary syndrome (ACS). However, none of these studies have included data on Bangladesh. Hence, we aimed to find out the SES among the patients with ACS admitted in a district-level general hospital of Bangladesh.Methods: All the patients with a diagnosis of ACS admitted from March 2016 to February 2017 in the Cardiology department of 250-bedded General Hospital (Abdul Malek Ukil Medical College & Hospital), Noakhali were enrolled in this study. Data on demography, risk factors and SES parameters of the patients was screened and recorded with the help of a pre-defined questionnaire. Socioeconomic profile of the patients was defined according to modified Kuppuswamy SES scale.Results: A total of 366 patients were included (mean age 56.6 ± 11.5 years, 261 male and 105 female). Most of the patients had multiple risk factors like smoking, hypertension, diabetes, dyslipidemia and family history of cardiovascular disease. 80.1% (n=293) of the studied patients were from lower socio-economic class followed by 18.3% (n=67) from middle class and only 1.6% (n=6) were from upper class.Conclusion: This study found that most of the patients admitted due to ACS in a district-level general hospital of Bangladesh are from lower socio-economic class. These findings could be useful to draw the attention of health authorities towards people of lower socio-economic class and to adopt preventive strategies for them against ACS.Cardiovasc. j. 2017; 10(1): 17-20